Beyond Citations: Measuring Novel Scientific Ideas and their Impact in Publication Text - Arts, Sam; Melluso, Nicola; Veugelers, Reinhilde (The Review of Economics and Statistics, 2025)
New scientific ideas drive progress, yet measuring scientific novelty remains challenging. We use natural language processing to detect the origin and impact of new ideas in scientific publications. To validate our methods, we analyze No-bel Prize-winning papers, which likely pioneered impactful new ideas, and lit-erature review papers, which typically consolidate existing knowledge. We also show that novel papers have more intellectual neighbors published after them, indicating they are ahead of their intellectual peers. Finally, papers introducing new ideas, particularly those with greater follow-on reuse, attract more citations.